Effect of Steviol Glycosides on Human Health with Emphasis on Type 2 Diabetic Biomarkers: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Camilla Christine Bundgaard Anker; Shamaila Rafiq; Per Bendix Jeppesen (2019)
The natural sweetener from Stevia rebaudiana Bertoni, steviol glycoside (SG), has been proposed to exhibit a range of antidiabetic properties. The objective of this systematic review was to critically evaluate evidence for the effectiveness of SGs on human health, particularly type 2 diabetic (T2D) biomarkers, collecting data from randomized controlled trials (RCTs). Electronic searches were performed in PubMed and EMBASE and the bibliography of retrieved full-texts was hand searched. Using the Cochrane criteria, the reporting quality of included studies was assessed. Seven studies, nine RCTs, including a total of 462 participants were included. A meta-analysis was performed to assess the effect of SGs on following outcomes: BMI, blood pressure (BP), fasting blood glucose (FBG), lipids, and glycated hemoglobin (HbA1c). The meta-analysis revealed an overall significant reduction in systolic BP in favour of SGs between SG and placebo, mean difference (MD): -6.32 mm Hg (-7.69 to 0.46). The overall effect of BMI, diastolic BP, FBG, total cholesterol, and highdensity lipoprotein cholesterol (HDL-C) was a non-significant reduction in favour of SGs, and a non-significant increase in low-density lipoprotein cholesterol and triglyceride, while no significant effect of HbA1c was found. Heterogeneity was significant for several analyses. More studies investigating the effect of SGs on human health, particularly T2D biomarkers, are warranted.